Cytology with rapid on‐site examination (ROSE) does not improve diagnostic yield of EUS‐FNA of pancreatic cystic lesions. Issue 11 (29th July 2019) - Estrada, Paul; Benson, Mark; Gopal, Deepak; Buehler, Darya; Pfau, Patrick
Abstract: Background: Cytology with rapid on‐site evaluation (ROSE) has been shown to increase the diagnostic accuracy of endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) for solid pancreatic lesions. No data exists on the need for rapid onsite cytology in the evaluation of pancreatic cystic lesions (PCLs). The purpose of this study is to determine whether onsite cytology impacts the diagnostic yield of EUS‐FNA of PCLs. Methods: We prospectively examined all patients with PCLs who underwent EUS‐FNA without onsite cytology over a 6‐month period and compared this to a historical cohort of patients with PCLs who underwent EUS‐FNA with ROSE in the previous 6 months. Comparison was made between the two groups based upon patient demographics, EUS cyst characteristics, and FNA fluid & cytopathology results. Results: A total of 100 EUS‐FNA exams for PCLs were identified: 46 with ROSE and 54 without onsite cytology. The majority of cytology findings were negative or nondiagnostic, 87.0% in the ROSE group, 77.8% in the group without onsite cytology. There was no difference using EUS‐FNA without onsite cytology compared to ROSE when measuring total diagnostic yield (22.2% vs 13.0%, P = .30), number of nondiagnostic specimens (50% vs 54%, P = .69), and number of needle passes (1.51 vs 1.57, P = .68). Conclusions: (a) The majority of cytology results from EUS‐FNA of cystic lesions are negative or nondiagnostic. (b) Having rapid onsite cytology evaluation of cystic lesions does not affect the number of needle passes nor diagnostic yield and is thus not recommended.